Combining Value and Momentum: Nordic Evidence - Huhta-Halkola, Topi (My University, 2018)
This Master´s thesis examines whether value and momentum strategies have been profitable in the Nordic stock markets from 1993 to 2017 and if combining the value and momentum can improve the pure-play strategies. Additionally, and most importantly, it is researched whether combining value and momentum into a more sophisticated combination portfolio can improve the results even further. By using Nordic data and a new time period, additional contribution is added to the existing research. Additionally, the combination of momentum and value is studied in a more detailed portfolio implementation manner than in Asness et al. (2013). Similar portfolio creation methods are used as in Fisher et al. (2016) but additionally long-short portfolios are examined. The results indicate that value and momentum anomalies existed in the Nordic stock markets during the time period, although value is driven mostly by the smaller stocks. Simple 50/50 allocation improves portfolio performance significantly which is further improved by combining value and momentum into a more sophisticated combination portfolio.
Keywords: value; momentum; portfolio implementation; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|